Different pulmonary adenocarcinoma growth patterns significantly affect survival. (March 2022) - Heldwein, Matthias B.; Schlachtenberger, Georg; Doerr, Fabian; Menghesha, Hruy; Bennink, Gerardus; Schroeder, Karl-Moritz; Schaefer, Stephan C.; Wahlers, Thorsten; Hekmat, Khosro
Abstract: Objective: Adenocarcinoma (AC) is the number one pathological entity of lung cancer with approximately 30–40% of cases. It is known to be heterogeneous and has 5 histopathological growth patterns. We evaluated the long-term survival rates of patients with predominant subtypes. Methods: 290 patients with AC underwent pulmonary resection between 2012 and 2017 at our institution. We excluded all patients with lymph node involvement and distant metastases. Hence, 163 patients were included for further analysis. Predominant growth pattern was defined if more than 10% of cells showed a growth pattern. 1, 3, and 5-year survival rates were evaluated. Survival was assessed by Kaplan-Meier curves and the Cox proportional hazards model was used to identify prognostic factors for overall survival. Results: Predominant growth patterns >10% were compared to <10% growth patterns of the same subtype. 1-year, 3-year, and 5-year overall survival rates of patients with predominant solid tumor growth >10% differed significantly from patients with <10% (88.4% vs. 97.6%, p = 0.04; 65.8% vs. 87.4% p = 0.001, 36.4% vs. 65.9% p = 0.01). Survival rates did not differ between >10% papillary and acinar growth compared to <10%. Kaplan-Meier curves showed reduced overall survival for patients with solid tumor growth >10% (log-rank 0.002). Solid tumor growth >10% was an independent prognostic factor for worse long-term survival (Hazard ratio: 3.05, p = 0.01). Conclusion: Our study demonstrates that the presence of a predominant solid pattern in pulmonary adenocarcinoma is a factor for an unfavorable prognosis. This should be kept in mind in daily clinical practice. Highlights: Adenocarcinoma (AC) is the most frequent entity of lung cancer 30–40% of cases. AC is known to be heterogeneous and has five histopathological growth patterns. There was a correlation of long-term survival and histopathological growth pattern. Solid growth pattern is an independent factor for an unfavorable prognosis. Multimodal therapy for patients with solid patterns should be critically examined.